2020
DOI: 10.1158/0008-5472.can-19-3068
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Maintenance Mechanisms Define Clinical Outcome in High-Risk Neuroblastoma

Abstract: ◥Neuroblastoma is a childhood cancer with heterogeneous clinical outcomes. To comprehensively assess the impact of telomere maintenance mechanism (TMM) on clinical outcomes in highrisk neuroblastoma, we integrated the C-circle assay [a marker for alternative lengthening of telomeres (ALT)], TERT mRNA expression by RNA-sequencing, whole-genome/exome sequencing, and clinical covariates in 134 neuroblastoma patient samples at diagnosis. In addition, we assessed TMM in neuroblastoma cell lines (n ¼ 104) and patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(138 citation statements)
references
References 49 publications
6
122
0
Order By: Relevance
“…ATRX mutations were identified in 55% of the ALT-positive neuroblastomas. In line with this observation, an ATRX mutation frequency of 60% was reported in a parallel study 46 . The most frequent type of ATRX mutations were large deletions.…”
Section: Discussionsupporting
confidence: 71%
“…ATRX mutations were identified in 55% of the ALT-positive neuroblastomas. In line with this observation, an ATRX mutation frequency of 60% was reported in a parallel study 46 . The most frequent type of ATRX mutations were large deletions.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies, using less-than-specific means of identifying ALT, suggest that ALT neuroblastomas have distinct clinical behavior such as older age at diagnosis, protracted disease progression, and poor response to chemotherapy (30)(31)(32). Employing more specific ALT markers, especially the robust telomeric DNA C-circle assay, we showed that ALT activation occurs in ~25-30% of high-risk neuroblastomas with or without ATRX genomic alterations (29). Patients with ALT neuroblastoma have very poor long-term survival and are often non-salvageable following progression or relapse (29).…”
Section: Introductionmentioning
confidence: 81%
“…Neuroblastoma patients stratified as highrisk continue to have poor outcomes, with an overall survival rate of ~ 50% with current comprehensive therapy (24)(25)(26). Using next generation sequencing and molecular approaches, we and several other groups observed that most common genomic alterations in high-risk neuroblastoma (MYCN amplification, TERT rearrangements, and ATRX genomic alterations) converge on activating telomere maintenance mechanisms (20,(27)(28)(29). We have recently shown that telomere maintenance mechanisms (TMM) define clinical outcome in high-risk neuroblastoma, irrespective of currently employed risk factors, suggesting that TMM are pivotal for neuroblastoma pathogenesis and may potentially provide therapeutic targets (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-risk neuroblastoma is broadly subdivided into two major cohorts: younger patients (toddlers) whose tumors show MYCN amplification, 1p deletion and TERT overexpression; and older patients whose tumors harbor 11q deletion, occasionally along with other recurrent segmental chromosomal alterations (SCAs), maintain chromosome ends via the alternative lengthening of telomere (ALT) mechanism, and generally show a slightly more inflamed TME [8][9][10][11]. It remains unknown if these or other genomic alterations are associated with anti-GD2 efficacy or how they may coordinate immune escape.…”
Section: Accepted Articlementioning
confidence: 99%